How empathic are vegan medical professionals compared to others? Leads from a paper–pencil-survey. Issue 5 (May 2018) - Kessler, Christian; Michalsen, Andreas; Holler, Sophie; Murthy, Vijayendra; Cramer, Holger
Abstract The aim of this survey was to examine differences in personality profiles among 198 vegan (n  = 64; 32.3%), vegetarian (n  = 78; 39.4%) and omnivore (n  = 55; 27.8%) medical professionals. Outcomes were motives for the nutritional approaches, WHO QoL-BREF, Big Five SOEP Inventory, Portraits Value Questionnaire, and Empathizing Scale. Regarding motives for particular diets, omnivores rated influence of guardians (p  < 0.001), physical health (p  = 0.017) and food taste (p  = 0.001) as more and love of animals as less important (p  < 0.001) than vegans and vegetarians. Vegans and vegetarians consumed less coffee (p  = 0.007) and alcohol compared to omnivores (p  = 0.017). The duration of adhering to a specific diet was significantly shorter in vegans. Data suggest that vegan medical professionals do not differ from vegetarians or omnivores regarding empathy, values or personality traits. Differences to a related internet sample were observed for a number of outcomes. Given the small sample size and potential selection bias through the specific subpopulation attending a plant-based nutrition conference, further studies are warranted to confirm these results. Particularly, potential reciprocities between empathy and individual nutritional choices deserve further attention.